The Influence of Surface Tension on Liquid Atomization - Melaniuk, M.; Orzechowski, Z. (Engineering Transactions, 1978)
The function of surface tension during liquid atomization has not been thoroughly investigated and the existing data on this problem are contradictory. The aim of this paper is to present the effect of surface tension on macro- and microscale parameters of an atomized jet. Experiments were carried out using two types of liquid with considerably different surface tension but of the same density and viscosity. To this aim a simple swirl atomizer was used in experiments while the average axial velocity of the liquid outflow was of the order of some scores of metres per second. It has been shown that as surface tension decreases, the radial distribution of density of droplets evidently changes. It has been also proved that surface tension does not effect the atomization spectrum.